Epidemiology, potential risk factors and outcome of black fungus during COVID-19 pandemic: a concurrent prospective study at a dedicated COVID-19 hospital of North India - Mithilesh Kumar; Shipra Saini; Lokesh Parashar; Jaseetha Sasidharan; Pooja Goyal; Ratan Prakash Dhir (Journal of the College of Community Physicians, 2022)
Introduction: As the number of COVID-19 patients increased during second wave, a steep rise of patients with mucormycosis was found in all parts of India.